Urinalysis: diagnostic performance of urine dipstick compared to an automated microscopic method - San Miguel Garay, Erik Alejandro; Llaca Díaz, Jorge M.; Robles Espino, Diana G; Díaz Chuc, Erik A.; Luna Falcón, Claudio Fabrizio; Ayala de la Cruz, Sergio (2023)
Introduction: Urinalysis is one of the most important clinical laboratory tests because numerous pathologies can manifest or be suspected through this test. Although the previous reports mention that urinary microscopy is a fundamental part of urinalysis for diagnostic support of various conditions, there is a debate about the utility of this test section in a certain patient population. The aim of this study was to determine the diagnostic performance of the urinary dipstick analysis and the potential risks of false-negative (FN) results.